The relationship of MISC’s share price performance with earnings, crude oil price and world population / Siti Nor Hamizah Baharzam Shah - Baharzam Shah, Siti Nor Hamizah (Faculty of Business and Management, 2006)
The purpose of the study is to examine the relationship between the independent variables (earnings, crude oil price, and world population) with the dependent variable (share price). This study also to identify which of the independent variable has a strong relationship with the share price. The data used for 7years from 2000 till 2006 and been analyzed using SPSS. We want to see the affect of market forces "demand and supply" towards the share price performance. How does the economic concept influence the growth of the company's in terms of earnings, operational and others? Simultaneously we look forward to the significant of the earnings, crude oil price and world population to the MISC' share price performance. Whereas MISC is a shipping provider internationally, we broaden the scope into the global market. Findings show that all the independent variables have a relationship with the share price. Crude oil price has a strong relationship with the share price among the other independent variables. There is positive relationship between earnings and crude oil price with MISC's share price. Meanwhile there is negative relationship between world population and MISC's share price.